This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Use the principle that  when  lim x->0, if  u - >0 and v ->0 ,
     then Lim x->0 u / v =   lim  x ->0 ,  u' / v'       (limit of the ratio of derivatives)

So we use this principle twice in the following steps.

 \lim_{x \to 0} \frac{(Sin\ x- x) }{x\ Sin\ x}= \lim_{x \to 0} \frac{(Cos\ x- 1) }{(x\ Cos\ x+Sinx)}\\\\=\lim_{x \to 0} \frac{-Sin\ x }{(-x\ Sin\ x + Cos\ x+ Cos\ x)}\\\\= \frac{- 0 }{(-0+1+1)} = 0\\

  • Brainly User
see,in order to calulate the limit differentiate the given expression since limit is tending to 0
you willget differentiation of 1/x as -1/x^2 ans 1/sinx is cosecx and so differentiation of cosecx is -cosecx.cotx and now put x=0 and you willget the answer as 0